Composition-dependent electrochemical activity of Ag-based alloy nanotubes for efficient nitrogen reduction under ambient conditions. (20th October 2019) - Zhang, Qiwen; Shen, Yongli; Hou, Yufan; Yang, Liting; Chen, Baili; Lei, Zhen; Zhang, Weiqing
Abstract: The composition-activity relationship is highly desirable for electrocatalytic nitrogen reduction reaction (NRR) because it could guide the rational design of efficient NRR catalysts. In this work, the composition effect of Ag-based alloy nanotubes on electrocatalytic NRR activity is systematically investigated. It is found that, among AgAu nanotubes with atomic ratio from 8:1 to 1:2, Ag2 Au1 alloy nanotubes achieve the largest enhancement for NRR catalytic activity. Specifically, the NH3 production rate and faradaic efficiency of Ag2 Au1 nanotubes are 21.7 μg h −1 mgcat −1 and 3.8% at −0.30 V vs. RHE, respectively, which were 3.0 and 3.6 times higher than those of Ag nanowires. Compared with Ag2 Pd1 and Ag2 Pt1 nanotubes, Ag2 Au1 hollow nanotubes also exhibit a better NRR catalytic activity. Theoretical calculation results indicate that the negative ion characteristic of Au atoms in the Ag2 Au1 alloy is favorable for the adsorption and activation of N2 . Moreover, Ag2 Au1 nanotubes showed stable NH3 yield rate and faradaic efficiency up to 18 h, revealing its great potential for promising NRR electrocatalysis. Graphical abstract: Image 1